Analytical investigation of the effect of a deformable sliding layer on the dynamic response of seismically isolated structures. (October 2020) - Tsiavos, Anastasios; Haladij, Peter; Sextos, Anastasios; Alexander, Nicholas A.
Abstract: This paper aims to investigate the effect of the deformability of a sliding layer on the sliding displacement and acceleration response of structures subjected to harmonic and pulse ground motion excitations. A two-degree-of-freedom model is used for the simulation of the dynamic response of structures founded on sliding layers of varying deformability. The dynamic equilibrium of motion of the sliding response of the structure to the selected ground motion excitation is presented in a novel, generalized and dimensionless mathematical formulation which reduces drastically the complexity of the variables compared to the existing formulations. Based on this mathematical framework, the stick–slip behavior ranges of structures founded on a deformable sliding layer are determined and compared with the corresponding behavior ranges of structures founded on a rigid-plastic sliding layer. The combined effect of the flexibility of the isolated structure and the dimensionless ground motion amplitude on these stick–slip behavior ranges, the sliding displacement and the acceleration response of the structure is presented. The use of this deformable layer is beneficial for seismic and vibration isolation of structures as it leads to a significant reduction of their maximum acceleration response compared to the rigid-plastic sliding layer case.